A Christian Perspective on Explorations of Shared Narrative of Religions and Its Significance to Islamic Studies, Islamic Thought, and Well Living - Abraham Silo Wilar (Millati: Journal of Islamic Studies and Humanities)
This paper discusses the shared narrative of religions to Islamic Studies and Islamic Thought to find its content and relate it to the two fields to conduct research in the broader context. In discussing the proposed topic, two approaches are taken from two academic disciplines, history and theology. The approaches are historical trajectory and theology comparative. Each offers its way to deal with the topic to generate certain knowledge of the topic related to the fields and beyond. The topic offers melek agama (religious literacy) and well-living as its important consequences possible to offer to the public to make religion a source and contributor to the development of social order and well living. To describe what is stated above, it is started by discussing the two approaches to the shared narrative of religions. This discussion is designed as a theoretical platform where its contents may be implicitly seen. Then, the researcher address application of its contents.